The reasons for establishing the interest rate on overpayment resulting from the decision confirming overpayment – comments de lege lata and de lege ferenda - Paweł Majka (Prawo Budżetowe Państwa i Samorządu)
The subject of the study is an analysis of the legal regulations concerning the interest rate on overpayment resulting from a decision recognizing an overpayment. In the author’s opinion, there is no doubt about the validity of solutions regarding the interest rates on overpayments, including those resulting from decisions that confirm them. At the same time, the existing solutions in this respect have been assessed as raising doubts as to the date from which the interest should be calculated. The difficulty in interpreting the regulations is related to the need, raised in the case law and the doctrine, to assess only the subjective elements of the “contribution” to the delay in issuing a decision by the tax authority due to the conscious and intentional actions of the taxpayer. The paper proposes that in connection with the proposal to pass a new Tax Ordinance, the shape of legal solutions in this area be modified, taking into account the assumption that the taxpayer should not suffer the negative consequences of the flawed functioning of the public authority in terms of both law making and the application of the law.